La placenta y el cordón umbilical del feto papiráceo en la anemia drepanocítica - Castejón S, Drs. Olivar C; Molinaro V, María P; Scucces M, María G; Tesone, María G; Duque, Mónica; Quiroz, Daniel (Gaceta Médica de Caracas, 2020)
Analizar la placenta y el cordón umbilical de un embarazo gemelar diamniónico-monocoriónico complicado con anemia de células falciformes y muerte intrauterina fetal es el propósito de este estudio. Análisis macro y microscópico de regiones de la placenta y del cordón umbilical del feto muerto fueron realizados. To analyze the placenta and umbilical cord of a diamniotic-monochorionic pregnancy complicated with sickle cell anemia and fetal intrauterine death is the purpose of this study. Macroscopic and microscopic analysis of placental and umbilical regions was done of material obtained from a patient with sickle cell disease.